2011
DOI: 10.1007/s00018-011-0868-2
|View full text |Cite
|
Sign up to set email alerts
|

Homeostatic regulation of NCAM polysialylation is critical for correct synaptic targeting

Abstract: During development, axonal projections have a remarkable ability to innervate correct dendritic subcompartments of their target neurons and to form regular neuronal circuits. Altered axonal targeting with formation of synapses on inappropriate neurons may result in neurodevelopmental sequelae, leading to psychiatric disorders. Here we show that altering the expression level of the polysialic acid moiety, which is a developmentally regulated, posttranslational modification of the neural cell adhesion molecule N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 54 publications
2
12
0
1
Order By: Relevance
“…We envisioned that the primary neurons would tolerate external perturbations better when they were interconnected to each other and supplemented by tissue scaffolds and nutrients. Our hypothesis was supported indirectly by a previous report, in which ManNProp, a potent inhibitor of a polysialyltransferase (ST8SiaII) (41,46), was metabolized and expressed on cell membranes in hippocampal slice culture and in vivo, although at an extremely low efficiency, probably by another polysialyltransferase (ST8SiaIV) (7,47). The use of tissue culture was also hinted as a means of increasing the cellular tolerance to unnatural sialic acids and their precursors, although no data were presented (43).…”
Section: Mbt Methods For Metabolic Labeling: Feeding Ac 4 Mannaz To Hisupporting
confidence: 64%
See 1 more Smart Citation
“…We envisioned that the primary neurons would tolerate external perturbations better when they were interconnected to each other and supplemented by tissue scaffolds and nutrients. Our hypothesis was supported indirectly by a previous report, in which ManNProp, a potent inhibitor of a polysialyltransferase (ST8SiaII) (41,46), was metabolized and expressed on cell membranes in hippocampal slice culture and in vivo, although at an extremely low efficiency, probably by another polysialyltransferase (ST8SiaIV) (7,47). The use of tissue culture was also hinted as a means of increasing the cellular tolerance to unnatural sialic acids and their precursors, although no data were presented (43).…”
Section: Mbt Methods For Metabolic Labeling: Feeding Ac 4 Mannaz To Hisupporting
confidence: 64%
“…The glycans modulate a multitude of cellular functions, such as adhesion, differentiation, cell-cell interactions, and recognition of external molecules, by mediating intracellular signaling events and also, intercellular communications (2,3). The regulatory functions of glycans are also considered to be significant in neurons, and previous biological work has suggested the intimate involvement of glycosylation in neurite development, synaptic plasticity, and neural regeneration (4)(5)(6)(7). The functional modulation of neural celladhesion molecule (NCAM) with polysialic acid (PSA), in particular, has been a primary target in the investigation of glycan roles in neurons.…”
mentioning
confidence: 99%
“…158160 These lines of evidence indicate the feasibility of glycoengineering precursors, and highlight the potential for future development and optimization of neural scaffolds towards clinical translation.…”
Section: Synergy With Other Peripheral Nerve Regeneration Therapiesmentioning
confidence: 98%
“…[365,366] MGE can be used as at emplate for in vivo experiments,a nd has advantages over other approaches,f or example,k nock-out experiments of polysialyltranserases in mice.R ecently,i tw as shown that inhibition of NCAM polysialylation by ManNProp induces aberrant border formation and fiber tract outgrowth in the hippocampus of newborn mice (Scheme 14). [367] Presumably, homeostatic regulation of the quantity of polySia at restricted stages of development is essential for correct synaptic targeting and circuit formation during hippocampal development. MGE by ManNProp is au seful method to interfere with polysialylation and signal transduction in vivo.…”
Section: Aliphatic Modifications and Neuronal Growth And Differentiationmentioning
confidence: 99%